A guide to succeeding in the Annual Review of Competency Progression (ARCP). Issue 9 (September 2018) - Lai, Chee Wan; Cresswell, Adrian Ben
Abstract: Regular assessment forms an important component of competency-based training in modern medical careers. Satisfactory performance at the Annual Review of Competency Progression (ARCP) is essential for progression through surgical training. The e-portfolio is central to the ARCP process and much of the 'added value' required to excel at the ARCP will also support and furnish a rich and strong curriculum vitae, which will in turn pay dividends in terms of career progression. The ARCP is often a source of anxiety amongst trainees, but with adequate preparation and planning the process should be smooth and stress-free – this article seeks to outline and support the key steps of the process. In this article, we will describe the ARCP process and offer some tips on how to not only pass through this process unscathed, but also ideally bring the 'added value' required to build a strong portfolio and a competitive CV.